2017
DOI: 10.19044/esj.2017.v13n11p112
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Social Disclosures in Kenya: A Longitudinal Study of Firms Listed on the Nairobi Securities Exchange

Abstract: This study which was exploratory in nature aimed to examine the extent to which firms listed on the Nairobi Securities Exchange disclosure social responsibility information and also to determine company and corporate governance variables that influence the Corporate Social Disclosures (CSD) practice in Kenya. Data on the disclosure index and company characteristics were obtained from the annual reports of the respective companies. A relationship between the disclosure index and the various company characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
2
7
0
1
Order By: Relevance
“…While the Hausman test from the analysis favoured the fixed effect estimator (Chi 2 had a value of 27.49 and a Prob > Chi 2 = 0.000), some of the dummy variables (foreign association and industry) were omitted from the model since they remain constant over the period. Consequently the random effect results were used in the final analysis to overcome the deficiencies associated with the fixed effect results similar to Wachira (2017). As Kohler and Kreuter (2009) suggest the random effect estimator handles better models that contain timeinvariant variables that are usually omitted by the fixed-effects model.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…While the Hausman test from the analysis favoured the fixed effect estimator (Chi 2 had a value of 27.49 and a Prob > Chi 2 = 0.000), some of the dummy variables (foreign association and industry) were omitted from the model since they remain constant over the period. Consequently the random effect results were used in the final analysis to overcome the deficiencies associated with the fixed effect results similar to Wachira (2017). As Kohler and Kreuter (2009) suggest the random effect estimator handles better models that contain timeinvariant variables that are usually omitted by the fixed-effects model.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Researchers have used content analysis and disclosure indices to measure extent of disclosures (Wachira, 2017). This study used risk disclosure index.…”
Section: Risk Disclosure Indexmentioning
confidence: 99%
“…A positive impact of age, size and industry's sensitivity on Ethiopian companies' engagement in reporting of their social and environmental information were as expected, which then indicated that when a company gets older or bigger or environmentally sensitive, they were more likely to report their social and environmental practice. Given that these explanatory variables were more related with social visibility; firms wanted to be perceived as a good company for the society and gained a public confidence by disclosing their social and environmental information which in turn maintains their social contract; keeping their dominancy and enabled them to minimize evil eye on the company (Reverte, 2009;Knox et al, 2006;Aerts et al, 2006;Wachira, 2017;Ohidoa et al, 2016;De Burgwal and Vieira, 2014;Naser and Hassan, 2013). According to these results, legitimacy theory was relevant for Ethiopian companies, because they have reported to sustain their legitimacy or to avoid a legitimacy gap between the society and firm's operation.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Larger companies and older firms are more likely dominant in the society and thus these companies are expected to have larger and diversified stakeholders in their product market and across diversified geographical area (Knox et al, 2006;Aerts et al, 2006). Consequently, they will be highly visible for social activists or regulators and thus they will use social and environmental reporting as a way to enhance their legitimacy through establishing their social responsibility credentials which will reduce the pressure of public scrutiny (Wachira, 2017;Ohidoa et al, 2016).…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 99%